Peranan Media Sosial sebagai Intervening dalam Mengoptimalkan Orientasi Kewirausahaan dan Kinerja UMKM di Nagari Kinali - Pratiwi, Anggi; Mariyanti, Eka (CV. ITTC INDONESIA, 2024)
This study aims to determine the effect of entrepreneurial orientation on the performance of MSMEs in Nagari Kinali, and the use of social media as an intervening variable. Respondents in this study consisted of 83 MSME players in the culinary field. Researchers set four hypotheses that were tested to examine the effect of entrepreneurial orientation and social media on the performance of MSMEs in Nagari Kinali. The results showed that entrepreneurial orientation has a positive and significant influence on the performance of MSMEs in Nagari Kinali. In addition, social media also has a positive and significant influence on the performance of MSMEs in Nagari Kinali. However, the results also show that entrepreneurial orientation has a more dominant influence on MSME performance compared to social media variables. This study also highlights the importance of entrepreneurial orientation in improving MSME performance, although the role of social media cannot be ignored either. The implication of these findings is the importance of MSME players to pay attention to and developing entrepreneurial orientation in an attempt to improve their business performance in today's digital era.